Behaviour of precracked RC beams strengthened using the side-NSM technique - Shukri, A. A. (Elsevier Ltd, 2016)
The side near-surface mounted (SNSM) method is an alternative method used for applying fibre reinforced polymer (FRP) flexural strengthening on reinforced concrete (RC) beams. The SNSM method places the FRP grooves at the sides of the beam, rather than at the bottom in the normal near surface mounted (NSM) method. This research focuses on studying the performance of precracked RC beams when strengthened with the SNSM method. Six RC beams strengthened with the side-NSM (SNSM) method were tested in flexure. Precracked SNSM strengthened beams have reduced ultimate load by up to 3.3% and higher stiffness by up to 28.4% compared to non-precracked SNSM strengthened beams. The modes of failure for SNSM strengthened beams was identical for the precracked beams and the equivalent non-precracked beams. A simulation method based on the moment-rotation approach was also presented and was found to be reasonably accurate and able to simulate the change in stiffness caused by precracking.